(untitled) (Orfeu, 2022)
In order to address the role of martial and community bands for the social education and cultural memory of cities, this article presents oral narratives of two band masters who passed through the former Escola de Aprendizes Artífices de Campos, today called, the Federal Institute of Education, Science and Technology Fluminense, whose historic campus is Campus Campos Centro. Through the oral history of life methodology was possible to collect narratives resulting from social practices and experiences with music, which corroborated the connection of musical experiences and the construction of collective memories. Ricardo de Azevedo and Valmir da Conceição are two former students of the Institute, whose life trajectories are fundamental for implementing collective-cultural policies. Despite having followed different paths in music, both come from community bands, having become masters of reference and resistance for the culture of bands in the North Fluminense Region.